Associations between sleep habits and interference of premenstrual symptoms in athletic performance in Japanese adolescent athletes: a cohort study over a 2-year period. (2nd October 2020) - Takeda, Takashi; Yoshimi, Kana; Imoto, Yoko; Shiina, Masami
Abstract: Premenstrual symptoms are common problems among female high-school and college athletes. This prospective study investigated associations between sleep habits and interference of premenstrual symptoms in athletic performance among Japanese adolescent athletes. A school-based survey on menstruation and school life was conducted among 623 female high-school students in 2015 and 2016, and data from the two surveys were connected. In total, 262 students completed the questionnaire in both years. We recruited 108 of those students who were athletes with regular menstrual cycles. Participants completed a questionnaire about their premenstrual symptoms and lifestyle habits. The prevalence of short sleep duration (<8 h) was high (95.4%). The difference in premenstrual symptom severity in individual students between the first and second years was not significant ( p  > .05). Premenstrual symptoms were less associated with disturbance in 'athletic performance in training or competition' in the second year than the first. 'Longer sleeping time' in the first year was associated with lower risk of increased interference of premenstrual symptoms in athletic performance in the second year (odds ratio 0.982, 95% confidence interval: 0.970–0.994). Shorter sleep duration may therefore have an effect on premenstrual symptoms' interference with athletic performance among Japanese adolescents.